2017
DOI: 10.1016/j.ebiom.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Effect of Oral Microbiota in the Prediction of Mucositis During Radiotherapy for Nasopharyngeal Carcinoma

Abstract: BackgroundOral mucositis is probably the most debilitating complication that can arise in treating a patient with head and neck cancer. Little is known about the impacts of oral microbiota on the initiation and progression of mucositis.MethodsBased on 16S rRNA gene sequencing, dynamic changes in oral bacterial profile as well as correlations between the severity of mucositis and bacterial shifts during radiotherapy were investigated.FindingsOur results revealed that bacterial community structure altered progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
151
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(166 citation statements)
references
References 45 publications
7
151
1
7
Order By: Relevance
“…Although recent antibiotic use was not significant when incorporated into a multivariable analysis (RR 1.88 [95% CI: 0.77‐4.63]; P = .168), such an association may imply a potential role for the microbiota in OM development. Preliminary results from patients with head and neck malignancies treated with radiation indicate that the oral microbiota shift in patients who develop mucositis . Whether this change is correlative or causative is an area of active investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although recent antibiotic use was not significant when incorporated into a multivariable analysis (RR 1.88 [95% CI: 0.77‐4.63]; P = .168), such an association may imply a potential role for the microbiota in OM development. Preliminary results from patients with head and neck malignancies treated with radiation indicate that the oral microbiota shift in patients who develop mucositis . Whether this change is correlative or causative is an area of active investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, current therapeutic approaches provide only limited protection. Our increasing understanding of mucositis pathophysiology, as well as the importance of shifts in salivary function, and the microbiota composition offers exciting new avenues for novel strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…How, if, and where the oral microbiome contributes to this scheme was the subject of a study reported in this issue of EBioMedicine by Zhu et al (2017) who prospectively evaluated the relationship between the trajectory of changes in the oral microbiome and oral mucositis in nineteen patients being treated with radiation or concomitant chemoradiation for nasopharyngeal carcinoma (NPC). Thirteen of the studied subjects developed severe mucositis.…”
mentioning
confidence: 99%
“…However, some authors already reported that Saccharomyces cerevisiae significantly reduced E. coli O157:H7 growth in a dynamic multi-compartmental digestion system, possibly through a potential inhibitory role of ethanol produced by the yeast (149 Due to the low number of patients with mucositis and the variability of the microbiota among patients, we were not able to elucidate if mucositis was associated with specific changes in the microbiota that could promote MRE colonization. Taking into account a recent study reporting differences in the composition of the oral microbiota depending on the mucositis severity (154), it is likely that mucositis could also produce changes in the gut microbiota, which may impact MRE colonization levels. Further studies including more samples from patients developing mucositis should be necessary in order to elucidate a possible link between mucositis, microbiota and MRE colonization.…”
Section: Microbiota Dysbiosis and Mre Colonization And Persistence Inmentioning
confidence: 99%